HUBUNGAN PERAN ORANG TUA DAN RELIGIUSITAS DENGAN PERILAKU SEKSUAL BERISIKO PADA REMAJA DI DESA SEDAYULAWAS KECAMATAN BRONDONG - Halila, Fadia; Sholikhah, Siti; Susanti, Inta (Jurnal Keperawatan Malang, 2025)
ABSTRACT Halila, Fadia Hanan. 2025. The Relationship Between Parental Roles and Religiosity and Risky Sexual Behavior Among Adolescents in Sedayulawas Village, Brondong Subdistrict, Lamongan Regency. Undergraduate Thesis. Nursing Study Program. Universitas Muhammadiyah Lamongan. Advisors: (1) Hj. Siti Sholikhah, S.Kep., Ns., M.Kes., (2) Inta Susanti, S.Kep., Ns., M.Kep. Risky sexual behavior among adolescents is a significant public health concern due to its potential long-term consequences, including unintended pregnancies, sexually transmitted infections, and psychological disorders. Parental roles and levels of religiosity are believed to influence adolescents’ behavioral tendencies. This study employed a descriptive-analytic design with a cross-sectional approach. The population consisted of all mosque-affiliated adolescents in Sedayulawas Village, Brondong Subdistrict, Lamongan Regency, totaling 110 respondents selected through total sampling. Data were collected using structured questionnaires and analyzed using Spearman’s Rho correlation test via SPSS. Results showed that the majority of adolescents had a high level of religiosity (35.5%) and that parental roles were categorized as high (44.5%). No significant relationship was found between parental roles and risky sexual behavior (p = 0.978; r = -0.003). However, there was a very strong and significant relationship between religiosity and risky sexual behavior (p = 0.000; r = 0.899), indicating that higher religiosity is associated with a lower tendency to engage in risky sexual behavior. These findings suggest that religiosity serves as a strong protective factor against such behavior, while parental roles did not demonstrate a significant contribution in this context. Value-based religious interventions are recommended as a strategic approach to prevent risky sexual behavior among adolescents. Keywords: Risky Sexual Behavior, Parental Roles, Religiosity, Adolescents